Topical preparations from the Iraqi plant aloe vera and their efficacy in skin infections. - Marie K. Nidhal; Al-Khateeb H. Ekbal; Al-Waiz M. (College of Pharmacy / Mustansiriyah University, 2005)
The dermatological preparations consist of simple or compounded bases in which one or more active ingredients are dissolved or suspended .The plant Aloe vera is widely distributed in Iraq, in addition to it's tranditional use in the treatment of occasional constipation , it is also used to assist healing of wounds ,burns and psoriasis. In this study; the amount of aloin (the major component of the plant) in the dried juice of the Iraqi plant Aloe vera is determined and was found to be 15.4% w/w and it is the major compound responsible for the antimicrobial activity of the plant. Different ointment bases were used in this study to prepare topical preparations from the dried juice of the Iraqi plant with different concentrations and were found that 4%w/w sodium carboxy methyl cellulose gel base was the best formula using comparative diffusion study through the skin. The clinical study which is carried out in this research on 61 patients with skin infections (mainly Tinea corporis and Tinea cruris) showed that 4%w/w gel base formula of aloe gave significant improvement in comparison with those treated with nystatin and hydrocortison and proved the antipruritic and antiinflammatory action of the dried juice of the Iraqi plant Aloe vera without any adverse effect. Finally the expiration date of aloin in the selected formula is determined and was found to be ≈ 2 years.